An FPGA-based network system with service-uninterrupted remote functional update - Tze Hon Tan; Chia Yee Ooi; Muhammad Nadzir Marsono (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The recent emergence of 5G network enables mass wireless sensors deployment for internet-of-things (IoT) applications. In many cases, IoT sensors in monitoring and data collection applications are required to operate continuously and active at all time (24/7) to ensure all data are sampled without loss. Field-programmable gate array (FPGA)-based systems exhibit a balanced processing throughput and datapath flexibility. Specifically, datapath flexibility is acquired from the FPGA-based system architecture that supports dynamic partial reconfiguration feature. However, device functional update can cause interruption to the application servicing, especially in an FPGA-based system. This paper presents a standalone FPGA-based system architecture that allows remote functional update without causing service interruption by adopting a redundancy mechanism in the application datapath. By utilizing dynamic partial reconfiguration, only the updating datapath is temporarily inactive while the rest of the circuitry, including the redundant datapath, remain active. Hence, there is no service interruption and downtime when a remote functional update takes place due to the existence of redundant application datapath, which is critical for network and communication systems. The proposed architecture has a significant impact for application in FPGA-based systems that have little or no tolerance in service interruption.